O wybranych translokacjach komunikacyjnych w dyskursie religijnym - Wojtak, Maria (Stylistyka, 2020)
The article presents a characteristics of several contemporary communication phenomena transforming religious discourse in its Catholic version. The author understands discourse as the entirety of communication practices specific to a particular community of believers, which in the course of various interactions fixes and agrees relevant to this community content, preserves appropriate scenarios of communication behavior and rules for their completion by utterances and/or non-verbal means. The author emphasizes the peculiarity of the religious discourse that is open to transcendence. She limits the scope of the presented communication phenomena to the catechetical discourse, which now focuses on participation of the catechized people in the process of catechesis. The methods of catechesis should therefore take into account the spiritual needs of the believers. Catechesis formulated in this mode promotes communication experiments, especially the processes of movement, i.e. translocation of speech genres from the secular to sacred realm. According to the author these translocations are accomplished in new genre forms that maintain the memory of their basic genre code, but at the same time are subject to processes of transformation conducive to the creation of new genre patterns. Some of them do not have genre identifiers in the form of special names and are only a beginning of new conventions. Such status is attributed by the author to evangelization visiting card analyzed in the article. Some of them gain names and create a series that preserves the innovative principles of the genre. As an example, the author discusses messages called the heaventels. They are an adaptation of the SMS convention for simulated (stylized) communication of God as the sender to the man. Translocations are favourable to launching of the adaptation processes and formation of genre duplicates that make the input (secular) genre form more capacious and communicatively catchy.